CCR4 is expressed on infiltrating cells in lesional skin of early mycosis fungoides and atopic dermatitis. Issue 6 (26th March 2015) - Sugaya, Makoto; Morimura, Sohshi; Suga, Hiraku; Kawaguchi, Makiko; Miyagaki, Tomomitsu; Ohmatsu, Hanako; Fujita, Hideki; Sato, Shinichi
Abstract CCR4 is expressed on tumor cells of mycosis fungoides (MF) and Sézary syndrome (SS). In MF, most infiltrating cells in patches and plaques express CXCR3, while tumor cells express CCR4 in advanced stages. Poteligeo Test IHC (CCR4 staining kit) is a newly developed staining kit that can examine the presence of CCR4 expressed on tumor cells of adult T‐cell leukemia/lymphoma, peripheral T‐cell lymphoma and cutaneous T‐cell lymphoma before treatment of anti‐CCR4 antibody using paraffin‐embedded samples. In this study, we analyzed CCR4 expression in lesional skin of MF, SS, atopic dermatitis (AD) and psoriasis with this new kit. CCR4 was expressed on infiltrating cells in lesional skin of patch, plaque, tumor MF and SS, and the number of positive cells increased as the disease progressed. Immunohistochemistry with frozen sections also showed some positive cells scattered in the dermis, although the quality was not high enough to quantify positive cells. There were significant positive correlations between CCR4+ cells and serum lactate dehydrogenase levels. Interestingly, CCR4+ cells were also detected in AD skin, whose number was larger than that in psoriatic skin. Previous studies showed only scattered CCR4+ cells in skin samples by standard immunohistochemical staining. The new, sensitive CCR4 staining kit has revealed that CCR4 is expressed on infiltrating cells in lesional skin of early MF and AD as well as advanced MF and SS. These cells can be therapeutic targets for patients who are resistant to standard treatments.